Tradisi Asokan Pada Walimatul ‘Urs Tinjauan Terhadap Ketahanan Ekonomi Keluarga di Kecamatan Bilah Hilir Kab. Labuhanbatu, Prov. Sumatera Utara - Basir; Irwan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The people of Bilah Hilir District have a tradition called Asokan. Asokan is assistance in the form of basic materials or money to ease the burden on the householder. Even though this tradition has been implemented by the people of Bilah Hilir District for a long time, there are still a number of people who object to this Asokan Tradition because they are required to return the Asokan at least equivalent to the amount given. Thus this Asokan is not really a gift but rather a debt that must be paid in time. The aim of this research is to determine the impact of Asokan on the economic resilience of families in the Bilah Hilir District Community. The problem of this research can be formulated as follows: how does Asokan occur in Bilah Hilir District, what is the influence of Asokan on family economic security, and what is the law on Asokan in Bilah Hilir District according to Islamic Sharia. Primary data was obtained from interviews and distributing questionnaires. Secondary data obtained from literature studies related to research problems. The Askan tradition has an influence on the economic resilience of families in the Bilah Hilir sub-district community which has a relatively low economic level.